REOG BULKIYO DANCE: TRADITION AND HISTORICAL REPRESENTATION OF THE JAVA WAR - Hafida, Mellina Nur; Agung, Dewa Agung Gede; Widiadi, Aditya Nugroho (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
The Java War, often known as De Javasche Oorlog or Diponegoro War, was an event that had an impact on national and local history. The capture of Prince Diponegoro by the Dutch on March 28, 1830, resulted in many of his troops fleeing to remote areas to avoid Dutch capture. As a result of the escape they settled in an area, disguised as ordinary people. One of the places where Diponegoro's troops escaped was in Kemloko village, Nglegok sub-district, Blitar district. The mind of the soldiers who managed to escape had a work of art in the form of Reog Bulkiyo Dance. The purpose of this study was to determine the history of the formation of Reog Bulkiyo Dance, the characteristics of Reog Bulkiyo dance, the existence of Reog Bulkiyo dance. This research uses a historical method consisting of (1). Heuristics, (2). Criticism, (3). Interpretation, (4). Historiography. The approach is carried out using cultural anthropology and the theory of cultural forms according to Koentjaraningrat to understand the origin of the creation of Bulkiyo reog dance as a form of expression, a symbol of communication and humanity to fight Dutch colonialism. The results of this study show that there are several historical facts about the emergence of Bulkiyo Reog Dance in Kemloko Village, Nglegok Subdistrict, Blitar Regency. The characteristics of Bulkiyo reog dance are influenced by Javanese, Arabic and Chinese cultures, this can be seen from the attributes and equipment used, the existence of Bulkiyo reog dance is influenced by internal factors of the Genealogical Inheritance system, and external factors of support from the community, government, and academics.